Penyelesaian Sengketa Transaksi Bisnis Elektronik Commerce Melalui Internet - Anak Agung Bagus Sempidi Junior; Anak Agung Sagung Laksmi Dewi; Desak Gde Dwi Arini (Warmadewa Press, 2021)
Development of information technology through legal infrastructure and its regulation so that the use of Information Technology is carried out safely to prevent its misuse by taking into account the religious and socio-cultural values of the Indonesian people. . The research method uses normative legal research and problem approaches using statutory and conceptual approaches. The results of the study show that consumer legal protection in online Electronic Commerce business transactions is regulated through online sale and purchase agreements based on conventional formal and material terms accompanied by buying and selling transactions carried out electronically through computer media. Settlement of disputes in e-commerce business transactions via online, is carried out both non-litigation and litigation. The suggestion is to the Government, it is hoped that participation in solving problems is very important, if a case like this occurs between different countries, then the settlement of this problem must be determined which legal rules will be used to solve it. The purpose of this study is to determine legal protection for consumers in electronic commerce business transactions through online, and how to resolve disputes that occur in electronic commerce business transaction agreements through online